Improving Community Skills in Making Processed Fish Products in Paluh Kurau Village, Deli Serdang, North Sumatra - Muhammad Ridha Syafii Damanik; OK Sofyan Hidayat; Meilinda Suriani Harefa; Darwin Parlaungan Lubis (Tunas Geografi, 2021)
The purpose of this community service is to find and increase the income generate of Medan State University which has been designated as a Public Service Agency in 2018. When a government institution turns into a Public Service Agency, it will be required to be independent in financial management including in terms of income management. This community service activity is a continuation of the previous year, where the Department of Geography Education, has pioneered the sale of online fresh fish which is a source of income generation. In 2021, the business unit will develop its products not only in fresh fish products but also in processed fish products with high economic value. In addition, this activity aims to help partner community groups to produce processed fish products to be marketed in the Medan State University Business Unit.The stages carried out in this activity are to collaborate with partners. Furthermore, conducting a series of training and mentoring for partner groups so that they can produce processed fish products that are in accordance with standards so that they are worthy of being marketed. This training and mentoring process was carried out in Paluh Kurau Village, District of Perak, Deli Serdang Regency.The output of this activity is the availability of processed fish products which can increase the income of partner groups and become an income generator for Medan State University.Keywords: Business Unit, Processed Fishery, Income Generating